FRI0426 Response of the reactive species interactome to hypothermia induced raynaud's attack in primary raynaud and systemic sclerosis. (12th June 2018) - Eman Abdulle, A.; van Roon, A.M.; Smit, A.J.; Pasch, A.; van Meurs, M.; Bootsma, H.; Fernandez, B.O.; Feelisch, M.; van Goor, H.; Mulder, D.J.
Abstract : Background: Although the exact etiology of systemic sclerosis (SSc) remains unknown, a current hypothesis is that reactive species (including reactive oxygen species (ROS), reactive nitrogen species (RNS and reactive sulfur species (RSS)) play an important role in the pathogenesis. In addition, the chemical interactions between these molecules, also known as the reactive species interactome, may lead to the formation of more harmful free radicals, thus leading to more damage. We have previously shown a rapid free thiol increase in SSc patients during a cooling and recovery experiment, however the implications of RNS and RSS in this process remain uncharacterized. Objectives: The aim of the current study was to explore nitric oxide and sulfate response, as a measure of the unified reactive species interactome, during hypothermia induced Raynaud's attack in systemic sclerosis (SSc), primary Raynaud's phenomenon (PRP) and healthy controls (HC). Methods: Healthy controls (n=10), PRP patients (n=10) and SSc patients (n=10), all aged ≥18 years, were included. All SSc patients fulfilled the ACR/EULAR 2013 criteria. Fingertip photoelectric plethysmography was performed during a standardised cooling and recovery experiment. Patient characteristics were obtained and blood was drawn at four predetermined time points (T0, T1, T2 and T3). In addition to the previously mentioned free thiols, the following markers were also measured: nitros(yl)ated species, nitrite, nitrate, sulfate and the vascular leakage related molecules angiopoietin-1 and angiopoietin-2). Results: Our results revealed a significantly longer median duration of hypoperfusion and longer recovery time in SSc patients compared to PRP patients and HC. This coincided with stable levels of angiopoietin-1/angiopoietin-2 throughout the experiment. In regards to the thiol modification related molecules, (nitrate, nitrite and RXNO) an increased median level of nitrate (T2: median 29.6 µmol, range 21.99–41.70 µmol, p=0.041) was found in SSc patients. Correspondingly, the same trend was observed for the median plasma concentrations of sulfate (p>0.05 at all time points). Conclusions: We have previously shown an increase of free thiols in all patients during the reperfusion phase. This finding sheds new light on the possibility that processes related to oxidative thiol modification, are rapidly reversible. The current findings revealed also a trend in increased levels of nitrate and sulfate in SSc patients. Therefore, it is plausible that these markers of the redox system interact with one another through the same pathway, underlining the complexity of the redox interactome and suggesting potential novel approaches for therapeutic intervention. Disclosure of Interest: None declared